1998
DOI: 10.1104/pp.117.1.321
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Phosphoribulokinase from the Marine Chromophytic Alga Heterosigma carterae1

Abstract: In this study we characterized phosphoribulokinase (PRK, EC 2.7.1.19) from the eukaryotic marine chromophyte Heterosigma carterae. Serial column chromatography resulted in approximately 300-fold purification of the enzyme. A polypeptide of 53 kD was identified as PRK by sequencing the amino terminus of the protein. This protein represents one of the largest composite monomers identified to date for any PRK. The native holoenzyme demonstrated by flow performance liquid chromatography a molecular mass of 214 ؎ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
2
11
2
Order By: Relevance
“…The PRK purified by this procedure had a high specific activity (300 units mg 21 ), which is comparable to the enzyme purified from spinach (Gardemann et al, 1983; Table I). V max and the respective K m values for ATP and Ru5P were rather similar to the enzyme from spinach and the cyanobacterium Synechocystis PCC7942 but differed markedly from data published for the haptophyte alga H. carterae (Hariharan et al, 1998).…”
Section: Production and Purification Of Recombinant Diatom Prkcontrasting
confidence: 70%
See 2 more Smart Citations
“…The PRK purified by this procedure had a high specific activity (300 units mg 21 ), which is comparable to the enzyme purified from spinach (Gardemann et al, 1983; Table I). V max and the respective K m values for ATP and Ru5P were rather similar to the enzyme from spinach and the cyanobacterium Synechocystis PCC7942 but differed markedly from data published for the haptophyte alga H. carterae (Hariharan et al, 1998).…”
Section: Production and Purification Of Recombinant Diatom Prkcontrasting
confidence: 70%
“…By gel filtration experiments, we found that the PRKs from different diatoms (O. sinensis, Coscinodiscus granii, and P. tricornutum) are homodimers with an apparent molecular mass of 44 kD/subunits on SDS gels (data not shown). This is identical to PRK enzymes from land plants but differs from previously published data for the PRK of the haptophyte Heterosigma carterae (Hariharan et al, 1998).…”
Section: Features Of the Prk From O Sinensiscontrasting
confidence: 59%
See 1 more Smart Citation
“…As a coastal-dwelling organism, H. akashiwo also contributes significantly to primary productivity within these critically important ecosystems [27]. Significant research on its morphology [28], physiology [29-31], molecular biology [32-34], toxicology [35,36], and biochemistry [37-39] define H. akashiwo as one of the most broadly studied non-diatomaceous stramenopiles. Much of this attention has been focused on events associated with chloroplast biology.…”
Section: Introductionmentioning
confidence: 99%
“…The two-fold symmetry that relates the top to the bottom layer creates the impression of a fourbladed pinwheel, with each pinwheel blade (e.g., lightly shaded subunits at right side of figure) corresponding to the dimer believed to represent the eukaryotic form of PRK. (Hariharan et al, 1998) suggests that this dithiothreitol (DTT)-stimulated enzyme is a tetramer of 53 kDa subunits. If such an assignment is confirmed, this protein would represent a new PRK quaternary structure.…”
Section: Molecular Characteristics and Sequences Of Prk Proteinsmentioning
confidence: 99%